A expansão do direito penal: os reflexos da influência midiática no processo de criminalização primária - SOUZA, Luciana Correa (Universidade Federal do Pará, 2018)
This work aims at analyzing the reflexes of the media influence in the process of primary criminalization on the criminal expansionism and its compatibility with the model of containment of the criminal repression of the Democratic Rule of Law established with the Federal Constitution of 1988. For this, In the first chapter, the approach of the theoretical basis necessary to understand the functioning of the mass media as components of the cultural industry, as well as the study of the media in the society of the spectacle, under the prism of the spectacularization of the news, is realized. In order to evidence the mercantile character of her on the crime. In the second chapter, we examine the processes of primary and secondary criminalization, as well as the development of the notion of selectivity and reflection on the latent functions of the penal system. Subsequently, in the third chapter, an appreciation of the process of construction of reality by the mass media is carried out, at which moment the media criminology and the discourse of media criminal populism in Brazil are discussed. At the end, in the fourth chapter, we study the reflexes of punitive populism in the legislative plane, for that, explores the bill 4.850/2016. Finally, based on the results of the study, the legitimacy of the manifestations of the Criminal Law of the enemy, in the legal system, is analyzed with the model of containment of criminal repression, typical of the Democratic Rule of Law and, particularly, with the Federal Constitution of 1988.